Closing the Loop between Clinical Practice, Research, and Education: The Potential of Electronic Patient Records - van der Lei, J. (Methods of Information in Medicine, 2002)
Objective: To discuss the possible contribution of electronic patient records in closing the loop among clinical practice, research and education.Results and conclusions: Applying Information and Communication Technology (ICT) to a given medical domain is not merely adding a new technique. When introduced into an environment, ICT will initially often emulate or resemble the already existing processes. When workers and researchers in that domain begin to appreciate the potential of ICT, this initial stage is followed by more fundamental changes in that domain that take advantage of the potential of ICT. To understand the scope of the potential changes enabled by electronic records, three principle changes need to be understood. First, data recorded in computer memories can be readily retrieved and re-used for a variety of purposes. Second, once data are available in computer memories, the data can be transported easily. Third, as physicians (and patients) are using computers to record medical data, the same electronic record can be used to introduce other computer programs that interact with the user. New usage of data, however, generates additional requirements. Thus the experience in developing decision support systems and analyzing observational databases feeds back into the requirements for electronic medical records.Each patient-physician encounter, each investigation, each laboratory test, and each treatment in medical practice constitutes, in principle, an experiment. Ideally, we learn from each experiment. Electronic medical records will facilitate research that relies on data recorded in routine medical practice. The potential and challenge, however, of Medical Informatics lies in its ability to close the loop among clinical practice, research, and education.
Keywords: Medical record systems; computerized automatic data processing; computer assisted decision making databases; medical informatics